Between-session reliability of portable isometric mid-thigh pull and countermovement jump tests in elite male ice hockey players from the Swedish Hockey League - Godhe, M.; Bergman, S.; Petré, H. (Sports, 2025)
This study investigated the test-retest reliability of strength and power-related measures assessed with a portable IMTP set-up and with CMJ in elite ice hockey players from the Swedish Hockey League. Twenty-two male ice hockey players (age: 26.8 ± 5.1 yr; height: 184.5 ± 3.9 cm; body mass: 88.6 ± 5.7 kg) participated in this study. The participants performed three maximal IMTP and CMJ trials on two separate occasions. Absolute and relative variables from the portable IMTP (force and rate of force development) and CMJ (force, power, velocity, impulse, jump height, time to peak force, time to peak power, concentric duration and eccentric duration) were obtained using force plates. Excellent reliability (ICC > 0.90; CV < 5%) was observed for multiple CMJ parameters, such as peak force (ICC = 0.94; CV = 2.7%), concentric and eccentric impulse (ICC = 0.96; CV = 1.4% resp. ICC = 0.95; CV = 2.9%) and CMJ peak power (ICC = 0.93; CV = 2.3%). IMTP peak force also demonstrated excellent reliability (ICC = 0.95; CV = 2.4%). IMTP rate of force development variables yielded reliability ranging from poor to moderate (CV = 12.9-54.6%). CMJ and portable IMTP provide highly reliable assessments of most strength and power-related variables in elite male ice hockey players. While absolute peak impulse, velocity and force, power and concentric duration displayed the highest reliability and should be prioritized, RFD variables require cautious interpretation due to high variability.